New SNPs in the EDG1 gene’s 5′UTR and their associations to Bali cattle meat quality traits - Sutikno, Sutikno; Priyanto, Rudy; Sumantri, Cece; Anwar, Saiful; Khaerunnisa, Isyana; Furqon, Ahmad; Jakaria, Jakaria (AIP conference proceedings, 2023)
Bali cattle, also known as Bos javanicus, are indigenous to Indonesia and have high productive and reproductive traits in harsh environments. These cattle have the potential to grow into high-quality beef cattle. According to studies, the beef marbling score is associated with the endothelium differentiation sphingolipid G-protein-coupled receptor 1 (EDG1) gene. The purpose of the research was to find three new SNPs in the EDG1 5’UTR that may be associated to traits related to meat quality in Bali cattle. We used 88 fresh blood samples for polymorphism analysis which consisted of Bali cattle (n = 30), Ongole grade (n = 20), Brahman (n = 20), and Limousin (n = 18), while for association analysis only used Bali cattle. The EDG1 gene’s polymorphism was examined using PCR and direct sequencing techniques, whilst the SAS 9.4 program’s General Linear Model (GLM) algorithm was used to examine the gene’s association with meat quality traits. The results of the genotyping identified three novel SNPs, c.-399C > T; c.- 273C > G; and c.-326C > G; which were polymorphic in Bali cattle and monomorphic in Ongole grade, Brahman, and Limousin. While SNP c.-312A > G was polymorphic in Brahman and Limousin cattle, it was monomorphic in Ongole grade and Bali cattle. Unfortunately, all of these SNPs are not associated with meat quality traits in Bali cattle. However, we suggest that further study with larger samples is needed for validation.